2013
DOI: 10.1002/ldr.2190
|View full text |Cite
|
Sign up to set email alerts
|

Combating Aeolian Desertification in Northern China

Abstract: Progress in combating aeolian desertification (land degradation resulting from wind erosion) has been achieved in an agro-pastoral ecotone of northern China since the mid-1980s. This paper reviews three common measures used to combat and control aeolian desertification in such regions. In addition, it introduces a case study on the recovery of a degraded semi-arid ecosystem to provide regional lessons and support theoretical and practical approaches to desertification prevention and reversal on a global scale.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(133 citation statements)
references
References 46 publications
(46 reference statements)
4
123
0
Order By: Relevance
“…Hevia et al (2007) found that notill showed more large aggregates and fewer fine aggregates than traditional tillage. This was also indicated by Gao et al (2015) and Wang et al (2015) over soil-conserving tillage in Northern China. Gomesa et al (2003) observed that soil erodibility by wind under traditional tillage was lower than in conservation tillage, since only a limited amount of material was available to wind erosion due mainly to crusting of the soil surface.…”
Section: Introductionmentioning
confidence: 69%
“…Hevia et al (2007) found that notill showed more large aggregates and fewer fine aggregates than traditional tillage. This was also indicated by Gao et al (2015) and Wang et al (2015) over soil-conserving tillage in Northern China. Gomesa et al (2003) observed that soil erodibility by wind under traditional tillage was lower than in conservation tillage, since only a limited amount of material was available to wind erosion due mainly to crusting of the soil surface.…”
Section: Introductionmentioning
confidence: 69%
“…Spatially, most land with wind-induced soil degradation (aeolian desertified land) are distributed in arid and semi-arid northern China where the annual rainfall is below 500 mm [7]. As Figure 2 shows, aeolian degraded lands are mainly scattered in (1) the semi-arid agro-pastoral ecotone of northern China (about 40.5% of total aeolian degraded land) where wind erosion and sand sheet incursions are responsible for most soil degradation; (2) the semi-arid steppe in the middle of Inner Mongolia (about 36.5% of total aeolian degraded land) where reactivation of fixed dunes and shifting sand incursions create the most soil degradation; and (3) the margins of oases and lower reaches of inland rivers in the arid region (about 23% of total aeolian degraded land) where reactivated fixed dunes cause most soil degradation [7]. Generally, human activities are considered to be one of most important factor contributing to wind-induced soil degradation [7,12].…”
Section: Wind-induced Soil Degradation In Northern Chinamentioning
confidence: 99%
“…The total economic loss due to wind-induced soil degradation has been estimated to be more than 54 billion Chinese Yuan (approximately 6.8 billion U.S. dollar) per year. About 170 million residents in arid and semi-arid northern China are threatened by wind-induced soil degradation [6]. Severe soil degradation generally decreases land productivity, which may result in local poverty, malnutrition, and disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent days, a range of desertification processes has been successfully analyzed and addressed, through the application of remote sensing techniques Miao et al, 2015;Wang et al, 2015;Torres et al, 2015;Yan et al, 2015;Xu et al, 2015). The land degradation of arid and semiarid zones, often called desertification when it is irreversible in form, and the main factors of this phenomenon being either climate-or human-induced, has been much debated since the mid-1970s (Rasmussen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%